Keberadaan Apartemen dan Pengaruhnya Terhadap Aktivitas Sosial dan Ekonomi Kawasan Seturan, Yogyakarta - Octasya Yusnindita Devi; Wisnu Pradoto (Jurusan Perencanaan Wilayah dan Kota, 2017)
As time goes by and the increase of the population temporarily or that will be settled in Yogyakarta, then the request will increase the willingness of land to be used for the provision of infrastructure facilities. The area is an example of an area which Seturan construction of apartments quite rapidly. The existence of this apartment is not only addressed to students but also to all walks of life. The existence of these apartments are bringing changes to the development of physical or socio-economic conditions of the Community area Seturan. research aims to assess the extent of the influence of the existence of the apartment to the development of the physical, social and economic areas Seturan, Yogyakarta. Data collection method using questionnaires and interviews on the Community area, and methods of analysis Seturan used are descriptive statistical analysis. Based on the research results can be noted that the existence of the apartment did not have much influence on the existence of an apartment taking action against economic and physical development. The most influence on the development of social conditions. The existence of physical development in the area because the area is SeturanSeturan areas of education including many arriving newcomers who will be growing every year so that people choose to open commercial activity for profit. An influential social development is in the presence of the apartment makes the area more prone, Seturan getting crowded, noisy and jammed. This is caused due to an apartment to make more and the increase of the population and then with increasing population made the region's increasingly congested and jammed. Cartilage often happens is prone to theft, because the area is so crowded with Seturan invite criminals to commit crimes.